Hybrid microwave sintering of fe-cr-mo - Nur Hidayah Abu Bakar (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Nowadays,stell are hardmetal and widely used in theindustry. The hardness metal of steel are high and corrosion resistance. Unifortunately, now the steel has a low mechanical properties and microstructure of particles because it easy to crack when subjected to high pressure. The existing Molybdenum alloys have moderate mechancial properties. Therefore, to enhance this mechanical properties hybrid micro wave technology (advanced manufacturing processing) was employed.